The relationship of certain physical and chemical factors to cooking and sensory evaluations of beef - Moe, D.R.; Kropf, Donald H.; Mackintosh, D.L.; Harrison, D.L.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
A group of 32 wholesale beef ribs, from cattle of known history, ranging in grade from high standard to high good, were used. A longissmus dorsi (rib eye muscle) sample was removed at the 12th rib and used to obtain color, pH, water-holding capacity and cooking data. Another longissimus dorsi sample from the 9-10-11th rib cut was chemically analyzed for protein, moisture and ether extract and buttons (spinous process-distal portion) were removed for penetrometer readings and calcium determinations. The 6-7-8th rib section was roasted, and cooking data (cooking time and losses), sensory evaluations by a subjective panel and objective measures were obtained by personnel of the Department of Foods and Nutrition. Correlation coefficients were calculated between various factors.
Keywords: Beef; Cooking data; Color; pH; Water-holding capacity